2020
DOI: 10.1007/s12671-020-01392-9
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness During Pregnancy and Parental Stress in Mothers Raising Toddlers

Abstract: Objectives Parental stress has been associated with adverse child outcomes and maternal functioning. Yet, maternal factors during pregnancy that can potentially protect against later parental stress, such as mindfulness, have not been studied. Therefore, we aimed to address the possible associations between prenatal mindfulness and levels of parental stress in mothers raising toddlers. Methods Women in the current study (n = 165) were prospectively followed from pregnancy until 3 years after childbirth, as par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…As suggested by Abasi et al (2021), the best interventions should be focused on enriching prenatal attachment behaviors such as fetal movement counting, touching the belly, and talking to the fetus. Moreover, other interventions like mindfulness-based prenatal programs could further have a positive effect on mothers' anxiety and increase strong healthy mother-infant bonding which may lead to healthier childhood development (Boekhorst et al, 2020;Sbrilli et al, 2020). Furthermore, adequate and functional perception of COVID-19 could enhance prenatal attachment.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested by Abasi et al (2021), the best interventions should be focused on enriching prenatal attachment behaviors such as fetal movement counting, touching the belly, and talking to the fetus. Moreover, other interventions like mindfulness-based prenatal programs could further have a positive effect on mothers' anxiety and increase strong healthy mother-infant bonding which may lead to healthier childhood development (Boekhorst et al, 2020;Sbrilli et al, 2020). Furthermore, adequate and functional perception of COVID-19 could enhance prenatal attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Bögels et al [ 56 ] suggested that mindfulness skills can reduce maternal stress, thereby reducing mothers’ fight or flight responses to parenting stress and improving their ability to make situationally aware decisions; thus, past studies have found that prenatal mindfulness improved the mother–infant relationship [ 57 ]. However, although the experimental group’s score for PBQ was lower than the control group’s score in our study, this difference was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…If the parenting demands outweigh a parent's personal resources, it results in parental stress (Sharda et al, 2019), defined as the psychological aversion toward the parenting demands (Deater-Deckard, 1998). Parental stress chiefly has three underlying components: parent-child relationship issues, parenting issues, and role restriction (Boekhorst et al, 2020). Environmental factors and parent and child characteristics significantly influence parental stress (Abidin, 1992).…”
Section: Research Backgroundmentioning
confidence: 99%